Passive Seismic Imaging of Lithosphere Structure At Active Tectonic Margins In Canada and New Zealand - Gosselin, Jeremy (Université d'Ottawa / University of Ottawa, 2021)
Our knowledge of Earth's structure and dynamics is owed, in large part, to techniques that allow us to infer the physical properties of rocks based on observations made near the surface. In particular, passive seismic imaging relies on natural sources of elastic wave energy (typically earthquakes) to illuminate Earth's interior. The frequency-dependent dispersive characteristics of surface waves from earthquakes provides a valuable constraint on the depth heterogeneity beneath the surface, which can be used to infer structure of the lithosphere (i.e., tectonics). The first part of this thesis develops novel tools for passive seismic imaging considering surface-wave dispersion. Specifically, Bayesian (probabilistic) methods are developed that provide rigorous uncertainty quantification. The ability to estimate the directional dependence of surface-wave speeds (i.e., seismic anisotropy) is demonstrated. Furthermore, a general approach for considering circular (wrapped) data, such as surface-wave phase measurements, is developed and applied to estimate the average dispersion between pairs of seismic stations. These ideas are applied to data recorded at seismic stations over British Columbia, Canada, to produce a large volume of data products that will help improve our understanding of the tectonics throughout the region. The second part of this thesis investigates the structural and mechanical conditions in subduction zones, where tectonic plates collide and one plate is thrust beneath the other. Specifically, a type of passive seismic imaging based on recordings of body waves from distant earthquakes (known as receiver functions) is used to infer subduction zone structure in relation to the coupling between tectonic plates. Receiver function data calculated for stations over the Cascadia subduction zone (southwestern Canada) suggest that episodes of slow slip on the plate interface occur in tandem with changes in mechanical conditions. Receiver function data calculated for stations over the Hikurangi subduction zone (New Zealand) suggest that stress and deformation along the margin are spatially linked to plate coupling. These results improve our understanding of the dynamics of these tectonic systems, including the seismic hazards that they pose.
Keywords: Seismology; Earth Structure; Inverse Theory; Tectonics